PERANAN PIMPINAN PERGURUAN TINGGI DALAM MENINGKATKAN MUTU DOSEN - Zulfakar, Zulfakar (Jurnal Paedagogy, 2020)
The implementation of higher education cannot be separated from national education as a continuing higher education from the previous education level. The 2012 Higher Education Law stipulates in article 1 point 18 that: Higher Education Standards are standard units which include national education standards, plus research standards and community service standards. Therefore, it is determined that lecturers are professional educators and scientists which has the main task of transforming, developing, distributing knowledge and technology including: education, research, and community service, which is known as the Tridarma Perguruan Tinggi. As a professional worker, lecturers should always be able to develop themselves, improve quality, both themselves and leaders. One of the integrated characteristics of higher education leadership is an educator. Lecturers who act as leaders must always maintain efforts to empower members of the organization such as lecturers who are an investment in higher education. The higher the lecturer's achievement, the higher the level of quality of higher education.